2020
DOI: 10.3389/fmicb.2019.02909
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Strategies for Exploring Bacterial Surface Glycans and Their Interactions With Glycan-Binding Proteins

Abstract: Bacterial surfaces are decorated with distinct carbohydrate structures that may substantially differ among species and strains. These structures can be recognized by a variety of glycan-binding proteins, playing an important role in the bacteria cross-talk with the host and invading bacteriophages, and also in the formation of bacterial microcolonies and biofilms. In recent years, different microarray approaches for exploring bacterial surface glycans and their recognition by proteins have been developed. A ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 106 publications
0
25
0
Order By: Relevance
“…We highlight the potential for a screen searching for novel chimeric topological mAbs, via grafting of known glycan-binding CDRs onto the 2G12 scaffold or by induction of domain exchange via mutation of the cross-over residues. In particular, anti-Bacterial glycan-targeting mAbs which tend to have desirable qualities—flexible recognition of multiple species due to targeting of “minimal” glycoepitopes Rollenske et al (2018) —as well as diagnostic microarrays, which have already characterized sets of mAbs and their glycan specificities Campanero-Rhodes et al (2020) , may serve as logical starting points. As described earlier, computational methods to predict glycan cluster topology and variability would greatly enhance these efforts.…”
Section: Glycoepitopes As Novel Antiviral Targets: a Perspectivementioning
confidence: 99%
“…We highlight the potential for a screen searching for novel chimeric topological mAbs, via grafting of known glycan-binding CDRs onto the 2G12 scaffold or by induction of domain exchange via mutation of the cross-over residues. In particular, anti-Bacterial glycan-targeting mAbs which tend to have desirable qualities—flexible recognition of multiple species due to targeting of “minimal” glycoepitopes Rollenske et al (2018) —as well as diagnostic microarrays, which have already characterized sets of mAbs and their glycan specificities Campanero-Rhodes et al (2020) , may serve as logical starting points. As described earlier, computational methods to predict glycan cluster topology and variability would greatly enhance these efforts.…”
Section: Glycoepitopes As Novel Antiviral Targets: a Perspectivementioning
confidence: 99%
“…These peculiarities have opened their use as targeting opportunities for cancer vaccines. Moreover, the specific binding of three members of the galectin family, that is, galectin 3, a chimera type, and galectins 4 and 8, having tandem-repeat-types ( Figure 7), has identified some of the above-discussed TACAs as ligands (Campanero-Rhodes, Sa Palma, Menéndez, & Solís, 2020). Galectins, which bind β-D-galactopyranoside residues, are widely expressed in epithelial and immune cells.…”
Section: Glyconanoparticles and Immune Cell Targeting: Why Nanotechmentioning
confidence: 99%
“…This section will highlight the pioneering work from the main author's laboratory together with recent investigations published since then. Of particular interest in this regard is the finding that some human sera of healthy individuals already contained antibodies against the TACAs, as determined using modern glycan microarrays (Campanero-Rhodes et al, 2020). This suggested that people have been somehow previously exposed to these biomarkers further highlighting the immunogenicity of glycans and their potential utility to generate immunotherapeutic agents.…”
Section: Glycodendrimers: Vaccines and Diagnosticsmentioning
confidence: 99%
“…bacterial surface glycans, peptidoglycans, glycoproteins for some species, and capsular polysaccharides (CPSs) are presented by both Gram-positive and Gram-negative bacteria. The former also contain lipoteichoic acids (LTAs) and wall teichoic acids (WTAs) while the latter contain lipopolysaccharides (LPSs) or lipooligosaccharides (LOSs) [1]. Some bacteria also produce exopolysaccharides (EPSs) which are a part of biofilm [2].…”
Section: Introductionmentioning
confidence: 99%